Comparison of T1-maps and late gadolinium enhancement images in the detection of Myocardial Fibrosis in Hypertrophic Cardiomyopathy - Baleia, Cláudia Neves Silvestre (2022)
Tese de Mestrado Integrado, Engenharia Biomédica e Biofísica, 2021, Universidade de Lisboa, Faculdade de Ciências